Cecal and blood fermentative indicators in broiler chickens fed Morus alba foliage meal in the ration - Mart?nez, Madeleidy; Sav?n, Lourdes; Dihigo, Luis Enrique; Hern?ndez, Yasmila; Oramas, A.; Sierra, F?lix; Montejo, Alba; Cueto, Milbis; Herrera, F?lix Rafael (Cuban Journal of Agricultural Science, 2010)
In order to study the cecal and blood fermentative indicators through the substitution of the corn ration by foliage of Morus alba (mulberry), 32 male broiler chickens of 21 d of age (HE21) were used. The birds were distributed according to complete random design into four treatments and eight repetitions, being a control (corn-soybean) and three levels of inclusion of mulberry foliage: 5, 10, and 15 %. The weight of the empty and full ceca and their length were measured. Besides, the concentration of total short-chain fatty acids (SCFA) and ammonia was determined, as well as the values of pH. Hemoglobin, hematocrit, and total cholesterol concentration were determined in blood. There was increase (P < 0.05) in the relative weights of the ceca (empty and full) using diets with mulberry foliage meal, compared with the control group (12.86, 13.93, and 13.96 vs 7.68 g/kg, respectively). The lengths of the right and left ceca differed (P < 0.05) between the control and the 10 % of substitution of mulberry foliage meal (17.88 vs 22.00 and 19.00 vs 23.25 cm, respectively, being superior in the latter. A similar performance (P < 0.05) had the concentration of total SCFA (49.60 vs 81.00 mmol/L). In the concentration of NH3 and the pH values, the control was superior (P < 0.05) compared with the rest of the treatments (2.43 vs 1.16, 1.32 vs 1.05 mmol/L and 6.74 vs 5.54, 5.58 and 5.70, respectively). The blood indicators did not show differences for hemoglobin and hematocrit. However, the cholesterol diminished with the inclusion of the mulberry foliage meal in the ration. It was concluded that with the inclusion of mulberry foliage meal up to 15 % in the ration of broiler chickens, the fermentative capacity of the ceca is increased, and it is proved the decrease in the cholesterol absorption provoked by this fibrous source. Key words: cecal fermentative indicators, blood indicators, broiler chickens, Morus alba foliage.